Investigation of rheological behavior of self-compacting and high performance composite concretes - Bispo, Rodrigo Andraus [UNESP]; Vicente, Gabriela Oliveira [UNESP]; da Silva Júnior, Gean Pereira [UNESP]; Benjamim, Daniel Ukuessunga [UNESP]; de Morais Alcântara, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2021)
This work describes proposed experimental methods for the characterization of concrete in fresh and hardened state, with the purpose of contributing to the experimental characterization of concrete. The main objective was to identify the rheological behavior of high performance (HP) and self-compacting (SC) concretes. Initially, a ordinary concrete composition was proposed, from which, silica fume (5, 10 and 15% in mass) and superplasticizer (0.6% in mass) were added to obtain HPC and SCC. Furthermore, for the self-compacting concretes, a modification in granular skeleton was proposed, with a reduction of total aggregate percentage by 22.73% in relation to the other compositions. The interference of these modifications was evaluated on the behavior of fresh concrete though the flow and slump test and hardened concrete through mechanical properties. The results showed that the modification in the granular skeleton of ordinary concrete contributed directly to the reduction of inertia factors of SCC, favoring the mobility conditions. For both self-compacting and high performance concretes, consistency and mechanical strength gain over ordinary concrete were influenced when the silica fume and superplasticizer concentration was increased, limiting your properties gains to these additions.
Keywords: Concrete; Rheology; Silica Fume; Superplasticizer